Waging peace: militarising pacifism in Central Africa and the problem of geography, 1962 - Hodder, Jake (Wiley, 2017)
Despite the discipline having undergone a ‘peace turn’ in recent years, the history of the peace movement itself remains curiously under explored by geographers. This paper retraces the World Peace Brigade and its collaboration with the Northern Rhodesian independence movement in 1962. I argue that the Brigade offers geographers important insights into how ideas of peace have been circulated, adapted and even resisted. The paper suggests that geography poses a distinct conceptual problem for peace movements, which must simultaneously operate beyond conventional forms of territorial politics while remaining sufficiently flexible in the political arena for their strength and relevance. In Central Africa this meant the Brigade developed two, ultimately incompatible, conceptions of peace: an internationalist one that stressed world community, and a local one that adapted pacifism for nationalist movements. I suggest this case study has two implications for peace research in geography. First, it encourages us to remain attentive to the big stories of peace and, specifically, the way in which the peace movement has been a historically important conduit for a range of internationalist ideas. Second, the histories of waging peace (peace armies, civil disobedience, etc.) allow us to critically interrogate the co-constitutive geographies of violence and nonviolence while retaining peace as a distinct category around which to promote political engagement.